The Effectiveness of Using Crossword Puzzle Games Through Student’s Vocabulary Mastery - Dwi Nur Hadiyansah Wijaksono S; Ainun Habiba Ramadani Siddik (JOEY: Journal of English Ibrahimy, 2022)
The purpose of this research was to find out whether there was an effect of using crossword puzzle games through students’ vocabulary mastery and the significant differences before and after using crossword puzzle games through students’ vocabulary mastery. The population of this research was eleventh students of Vocational High School 1 Banyuputih. XI AKL as the experimental class consisted of 25 students. For the sampling technique, the researcher used purposive sampling. In the getting data, it was obtained by using questionnaires filled out by students and used tests that divided into pre-test and post-test. This research method used quantitative research methods and conducted a pre-experimental design as the research design of this study with data testing using SPSS 16. Based on the analysis result of this research showed that the result of the T-test formula to test the hypothesis of this research insignificance 2 degree (α) of 5% is T-test (to) > T-table (table) (18.90 > 1.713). Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted that there is a significant difference between students’ vocabulary mastery before and after using crossword puzzle games.